Studi Strategi Operasional Agility Pada Bank Di Indonesia = A Study on Agility Operational Strategy of The Banks in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The objective of this research is to indicate difference of characteristic of competitive capability competitive priority and non financial busines performance between agile and non agile group. Competitive capability includes dimensions of technological leadership, employee knowledge and physical distribution network (branch office). Competitive priority consists of dimensions of service quality, service quality, service delivery, service flexibility and low cost. Non financial business performance includes business sustainability, quality of customer interface and productivity factor. Before showing its characteristic difference, the banks are classified into groups based on competitive priority using hierarchical cluster analysis and are called service strategic group. This result was done in banking industry in Indonesia. Sample in research is 48 banks of 128 banks operating in Indonesia. This research uses purposive mail survey. Result of cluster analysis is two clusters: agile and non agile group. The result of this research indicated significant difference in competitive capability, competitive priority and non financial business performance between agile and non agile group.